Rethinking Work and Energy: A Cross-Context Phenomenological Inquiry in Physics Classrooms - Karim, Siti Nurqualbiah Mat; Jamalulai, Fajriani; Gargar, Kim A (Schrödinger: Journal of Physics Education, 2026)
Purpose of the study: This study aims to explore and analyze the lived experiences of students and teachers in learning the work and energy topic using a phenomenological approach across Indonesian and Malaysian contexts, in order to understand how conceptual understanding is constructed within different pedagogical and socio-cultural settings. Methodology: This study employed a qualitative phenomenological design with purposive sampling. Data were collected using validated in-depth interview guidelines (content validity index = 0.81), classroom observations, and document analysis. Data were transcribed verbatim and analyzed through phenomenological procedures (horizontalization, coding, thematic clustering, textural–structural description, cross-case analysis) with triangulation, member checking, audit trail, and researcher reflexivity. Main Findings: Students in both Indonesia and Malaysia predominantly experienced work–energy learning as formula-based and computational. Conceptual understanding was fragmented, with weak causal integration between work, kinetic energy, potential energy, and conservation principles. Procedural competence exceeded qualitative reasoning ability. Mathematical ability strongly influenced confidence and performance. Pedagogical practices in both contexts emphasized numerical problem-solving, reinforcing algorithmic thinking over reflective and conceptually integrated understanding. Novelty/Originality of this study: This study introduces a cross-context phenomenological analysis of work–energy learning in Indonesia and Malaysia, moving beyond diagnostic measurement of misconceptions toward exploring students’ and teachers’ lived experiences. It advances existing knowledge by revealing how pedagogical structures and socio-cultural classroom dynamics systematically shape computational-dominant understanding, offering a deeper interpretive framework for conceptual reform in physics education.